Recent Progress in Sleep Quality Monitoring and Non-drug Sleep Improvement - Chi, Jing; Cao, Wei; Gu, Yan (Frontiers in Human Neuroscience, 2020)
Insomnia is one of the most common health risk factors in the population as well as in clinical practice, which is associated with genes, neuron, environment, behavior, and physiology, etc. This review summarizes the recent progress in sleep quality monitoring and non-drug sleep improvement. The innovation of wearable and effective invention suggests a new approach and have deep implications towards sleep improvement and yet, the health care innovation system is also facing the challenge to foster the progress.